Negative photoconductivity in Cs4PbBr6 single crystal. Issue 25 (19th June 2020) - Yuan, Ye; Yao, Qing; Zhang, Jie; Wang, Kaiyu; Zhang, Weiwei; Zhou, Tianliang; Sun, Haiqing; Ding, Jianxu
Abstract : Negative photoconductivity is firstly observed in large size Cs4 PbBr6  single crystal that grown from Cs-rich solution. The Br vacancy and free excitons are responsible for this novel phenomena. Abstract : Zero-dimensional (0D) inorganic perovskites, particularly Cs4 PbBr6, have been attracting wide attention due to their excellent photoluminescence (PL) efficiency and spectral color purity. The PL origin of Cs4 PbBr6 and the underlying photophysics, however, draw intense debate and remain controversial. Revealing the photo-excited carrier generation, separation, and recombination, as well as the roles that mobile ions play, is crucial and helpful to deeply understand the photo-physical property. Photoconductivity is one of the effective approaches to closely explore the photophysics. In this study, high-purity Cs4 PbBr6 single crystals were grown from Cs-enriched solutions. Negative photoconductivity was first observed in Cs4 PbBr6 through Au-crystal-Au photo-detectors, and the photocurrents under high illumination power are similar to those of the diode. It is considered that the built-in electric field produced by the charged excitons combined by the neutral excitons and vacancies of Br (VBr + ) are responsible for the eccentric negative photoconductivity phenomena because of strong Coulomb interactions and low VBr + formation energy in Cs4 PbBr6 .